Two dimensional modelling of the flood zones in the Vistula River Valley in Warsaw - Magnuszewski, Artur; Gutry-Korycka, Małgorzata; Szydłowski, Michał (IGiPZ PAN, 2009)
When estimating the reach of the flood zones, a mathematical model that describes the flood wave propagation, as well as the digital elevation models can be used. In this study, a two step approach has been applied. In the first step, in order to find the most relevant flooding areas, a one dimensional hydraulic model HEC-RAS has been used, which assumes steady state flow conditions and a discharge of Qp 1% = 7210 m3/s and Q p 0.1%= 9960 m3/s. The segment of the Vistula Valley analysed is 47.05 km long. In the second step, a smaller area has been analysed using the 2D hydraulic model of shallow water flow which is based on the Roe scheme of finite volume method.
24 cm
Keywords: Warsaw; Vistula river; flood zone maps; inundation modelling